2014
DOI: 10.5114/aoms.2014.43751
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitivity of human ovarian carcinoma and melanoma cells to γ-rays and protons

Abstract: IntroductionProton radiation offers physical advantages over conventional radiation. Radiosensitivity of human 59M ovarian cancer and HTB140 melanoma cells was investigated after exposure to γ-rays and protons.Material and methodsIrradiations were performed in the middle of a 62 MeV therapeutic proton spread out Bragg peak with doses ranging from 2 to 16 Gy. The mean energy of protons was 34.88 ±2.15 MeV, corresponding to the linear energy transfer of 4.7 ±0.2 keV/µm. Irradiations with γ-rays were performed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…These restrictions excluded 84 points from the original set of 369 data points. Data removed due to the restriction of (α/β) x < 30 Gy included all the reported measurements in some studies (Ristic-Fira et al 2011, Petrović et al 2010, Antoccia et al 2009, Sakamoto et al 1980, Keta et al 2014) or the removal of selected data points (Belli et al 2000, Bettega et al 2000, Blomquist et al 1993, Grosse et al 2014, Baggio et al 2002, Schettino et al 2001, Urano et al 1980). The restriction of LET d < 20 keV/μm excluded another two studies (Goodhead et al 1992, Wéra et al 2011) as well as selected data points from other studies (Belli et al 1989, 1992, 1993, 1998, 2000, Bettega et al 1998, Chaudhary et al 2014, Fiorini et al 2011, Folkard et al 1989, Ogheri et al 1997, Prise et al 1990, Schettino et al 2001, Schuff et al 2002, Sgura et al 2000).…”
Section: Methodsmentioning
confidence: 99%
“…These restrictions excluded 84 points from the original set of 369 data points. Data removed due to the restriction of (α/β) x < 30 Gy included all the reported measurements in some studies (Ristic-Fira et al 2011, Petrović et al 2010, Antoccia et al 2009, Sakamoto et al 1980, Keta et al 2014) or the removal of selected data points (Belli et al 2000, Bettega et al 2000, Blomquist et al 1993, Grosse et al 2014, Baggio et al 2002, Schettino et al 2001, Urano et al 1980). The restriction of LET d < 20 keV/μm excluded another two studies (Goodhead et al 1992, Wéra et al 2011) as well as selected data points from other studies (Belli et al 1989, 1992, 1993, 1998, 2000, Bettega et al 1998, Chaudhary et al 2014, Fiorini et al 2011, Folkard et al 1989, Ogheri et al 1997, Prise et al 1990, Schettino et al 2001, Schuff et al 2002, Sgura et al 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a wide range of non-surgical treatment modalities is used, such as chemotherapy, targeted therapy, immunotherapy, and radiation therapy [ 6 ]. Radical re-excision of the tumour bed in the case of cutaneous malignant melanoma is a central part of the surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, few works have been published about cells exposed to proton radiation and most of them refer to exposure at high proton dose (from 1 Gy up to more than 10 Gy), as expected, because the authors investigated radiosensitivity of tumor cell lines. These works, based on biological assays, reported that protons have a larger relative biological effectiveness (RBE) than photons (Keta et al 2014) and the RBE value increases as the cell position on the Spread Out Bragg Peak (SOBP) moves distally (Chaudhary et al 2014;Matsumoto et al 2014;Hojo et al 2017). In addition, Fourier Transform Infrared Spectroscopy measurements revealed chromatin fragmentation in adenocarcinoma PC-3 cells following proton irradiation (Lipiec et al 2014).…”
Section: Introductionmentioning
confidence: 99%